COMPARISON OF FREQUENCY OF WOUND INFECTION: OPEN VS LAPAROSCOPIC CHOLECYSTECTOMY - Siddiqui, Kiran; Khan, Abul Fazal Ali (Journal of Ayub Medical College Abbottabad, 2006)
Background: The objective of this quasi experimental study was to compare the frequency of wound infection between open cholecystectomy (OC) and laparoscopic cholecystectomy (LC) conducted in Surgical Unit IV, Jinnah Hospital Lahore from June 2005 to January 2006. Methods: 100 patients undergoing elective cholecystectomy for symptomatic gallstones were studied. The patients were allocated in the two groups of 50 each by simple random technique. Group-I underwent OC and Group-II underwent LC. The patients were then followed up for four weeks to pick up signs of wound infection. In case of infection, the degree of infection and the remedial measures done were documented and the results analysed. Results: In LC group there was only one case of Class- II wound infection i.e. 2%. In case of OC there were three cases of wound infection i.e. 6%. Out of these, two were of Class-III and one of Class-II. Conclusion: While there was no wound infection in cases of chronic Cholecystitis in both groups, the frequency of wound infection was three times as common in OC as compared to LC in Acute Cholecystitis / Empyema. Key words: Open cholecystectomy (OC), Laparoscopic Cholecystectomy (LC), Wound infection.